Adoption of Digitalization in SMEs Using the TOE Framework and Advanced Analyses - Risqi Arifia, Annastasya (Journal Economic Business Innovation, 2024)
Objective: The objective of this study is to investigate the influencing factors that lead to the adoption of digitalization in small and medium-sized enterprises (SMEs), taking into account the interaction of technological, organizational, environmental, and outside market dimensions based on the Technology-Organization-Environment (TOE) framework.Method: A quantitative approach was adopted that included using a structured survey to gather data from 200 SME managers from three main industries: manufacturing, services, and retail. For testing the relationships of TOE dimensions and digitalization adoption and the moderating effect of technological readiness, data were analyzed using Structural Equation Modeling (SEM).Results: It finds that all three dimensions of the TOE model, i.e., technological, organizational, and environmental, have a significan positive effects on SMEs' digital technology adoption. The study further establishes external market forces as a key mediator between the relationship of the dimensions and digitalization. It was discovered that the technological preparation level moderates the adoption phase, adding to the agility with which SMEs embody digital technologies.Originality: The significance of this research lies in the fact that it uses empirical evidence to exhibit how external market factors mediate the relationship between TOE dimensions and digitalization adoption. It emphasises the role of technological readiness and market forces in informing SMEs' digital transformation strategies, which has been largely overlooked in prior research.Implications: These findings hold significant implications for SMEs and policymakers alike. SMEs investment on in-house Technological Readiness enable digitalization, while innovative Digital Technologies adoption by SMEs would need favorable exogenous Environmental Mullions alignment from the Government Policymakers Future research can also consider more moderating variables and use longitudinal designs to capture the changing nature of digitalization in SMEs